2017
DOI: 10.3389/fmicb.2017.02300
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Dynamics in Dichloromethane-Contaminated Groundwater Undergoing Natural Attenuation

Abstract: The uncontrolled release of the industrial solvent methylene chloride, also known as dichloromethane (DCM), has resulted in widespread groundwater contamination in the United States. Here we investigate the role of groundwater bacterial communities in the natural attenuation of DCM at an undisclosed manufacturing site in New Jersey. This study investigates the bacterial community structure of groundwater samples differentially contaminated with DCM to better understand the biodegradation potential of these aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 89 publications
3
18
0
Order By: Relevance
“…We observed two distinctly defined taxonomic compositions between the two communities, shaped by geographic separation and differences in arsenic concentration. Our finding supports a previous study that identified similar spatial and concentration related differences in bacterial community response to a toxin [48]. Our study is the first of its kind to analyze changes to the gut microbiota of individuals in South East Asia, and lays the groundwork for future, more in-depth studies on the influence of arsenic on the health of the gut microbiome and overall human health.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed two distinctly defined taxonomic compositions between the two communities, shaped by geographic separation and differences in arsenic concentration. Our finding supports a previous study that identified similar spatial and concentration related differences in bacterial community response to a toxin [48]. Our study is the first of its kind to analyze changes to the gut microbiota of individuals in South East Asia, and lays the groundwork for future, more in-depth studies on the influence of arsenic on the health of the gut microbiome and overall human health.…”
Section: Discussionsupporting
confidence: 90%
“…Both communities shared selection for some arsenic volatilizing taxa like Desulfovibrionaceae, but each was possessive of its own unique assemblage of pathogenic bacteria and both showed higher selection for certain arsenic volatilizing bacteria that the other did not. As noted earlier, the observation of site specific compositional differences in response to a contaminant is not unique to this study [48].…”
Section: Discussionmentioning
confidence: 69%
“…Despite this potential drawback, similarly to the diversity estimates, relative BCC also showed only few differences at the phylum level. All samples are dominated by the phylum Proteobacteria, a result that corresponds to observations reported from other studies (Braun, Schröder, Knecht, & Szewzyk, ; Wright et al., ). Due to the fact that geochemical characteristics are the main drivers of BCC (Constancias et al., ), and since geochemical characteristics differ only slightly across sampling sites, we suggest that this results in a similar taxonomic community composition at the phylum level.…”
Section: Discussionsupporting
confidence: 89%
“…Among the most abundant bacterial members at the site (Figure 3), a number have been linked to hydrocarbon biodegradation processes and/or hydrocarboncontaminated environments. These include the Actinobacterial order iii1-15 (Morais et al, 2016), Anaerolineaceae (Kümmel et al, 2015;Liang et al, 2015;Rosenkranz et al, 2013), the Chloroflexi class GIF9 (Alfreider et al, 2002), the Elusimicrobiales order (Wright et al, 2017), Thermoanaerobacteraceae (Marozava et al, 2018), -Von Abercron et al, 2017;Morais et al, 2016;Yang et al, 2014Yang et al, , 2016, Rhodospirillaceae (Cui et al, 2008;Viñas et al, 2005),…”
Section: Bacterial Communitiesmentioning
confidence: 99%